Acquired Complete Atrio-ventricular Block Requiring Permanent Pacemaker in a Child with Viral Myocarditis - Kabbani, Mohamed S; Alsumih, Norah A; Alsadun, Sarah A; Altaweel, Hayan; Ghamdi, Saleh Al (Archives of Clinical and Medical Case Reports, 2019)
Myocarditis is an inflammation of the myocardium that can lead to necrosis and degeneration of myocytes. Viral myocarditis may affect children consequences. Complete atrioventricular block (CAVB) arise as a rare complication of acute myocarditis. Its occurrence in infants and children is uncommon, but can lead to serious complications. In this case report, we present a 29-month-old male, previously healthy, with a picture of acute myocarditis associated initially with junctional tachyarrhythmia that progressed later to persistent CAVB needing permanent pacemaker insertion.